Perancangan Iklan Layanan Masyarakat Untuk Mengurangi Kecanduan Game Pada Pelajar SMP - Rajab, Junaidi; Budiwaspada, Agung Eko; Minawati, Rosta (SPACEPRO: Product Design Jurnal, 2023)
Abstract The influence of the game is so great for Junior High School students, in which games can create addiction for them. As a result, they cannot manage their time well, skip their classes, and oftenly disturbed while studying because they constantly think about games on and on. The main cause is likely because of the psychology of junior high school students that still cannot control what they want wisely. As a result, their performance in studying will certainly decrease, which is resulted in their failure in academics. If this phenomena continues, it will surely impact their future in negative way. Therefore, it is necessary for the media to help junior high school students to be aware about the importance of managing their time, as well as giving the understanding that play games is not bad but they should know the boundary. Keywords: Public Service Ads, Games, Junior High School Students.